“Wening”: Towards a Contemplation of Javanese Women’s Self-Identity in The Painting of Dyan Anggraini Rais through an Art Criticism Approach - Handayani, Ayu Puji; Marianto, Martinus Dwi (Institut Seni Indonesia Yogyakarta, 2024)
This article discusses the artwork of Indonesian Woman Artist Dyan Anggraini Rais in The International Art Exhibition Dewantara Triennale 2023 #2 “Social Engagement & Sustainability at Jogja Gallery entitled “wening” as a medium for contemplation of the form of representation of Javanese Women’s self-identity through the Art Criticism approach as a form of appreciation and evaluation of the artwork through reading the interpretation of the visual semiotic code on the artwork. It is found that the Contemplation of Javanese Women’s Self Identity in Wening painting represents the character of Javanese Women’s identity which is seen as a meek figure, good character, nrima, manut, not messing around, but also firm and principled. This is visualized in the symbolization of the meaning of Dewi Sekartaji’s mask. These values have also been exemplified by Kartini’s struggle through women’s emancipation to demand justice for women through the realm of the public sector, especially in the field of education. These noble values should remain inherent and become a living representation for women in contemporary times, where at this time it is very possible for women’s accessibility to be able to enter the public sector to express themselves and build their identity through the various potentials that exist in women to continue to develop and be appreciated. The artwork “Wening” by Dyan Anggraini Rais is a form of self-reflection needed by each individual in this era, especially women, to get to know themselves better and realize the social construction that has shaped them so far. Artikel ini membahas karya seni lukis Perupa Perempuan Indonesia Dyan Anggraini Rais dalam Pameran Seni Rupa Internasional Dewantara Triennale 2023 #2 “Social Engangement & Sustainability di Jogja Gallery yang berjudul “wening” sebagai media perenungan bentuk representasi identitas diri Perempuan Jawa dengan menggunakan pendekatan Kritik Seni (Art Criticism) sebagai bentuk apresiasi dan evaluasi terhadap karya seni tersebut dengan cara membaca pemaknaan terhadap kode semiotika visual pada karya seni lukis tersebut. Hasil penelitian menunjukkan bahwa Kontemplasi Identitas Diri Perempuan Jawa dalam lukisan Wening merepresentasikan karakter jati diri perempuan Jawa yang dipandang sebagai sosok yang lemah lembut, berbudi pekerti luhur, nrima, manut, tidak main-main, namun juga tegas dan berprinsip. Hal ini divisualisasikan dalam simbolisasi makna topeng Dewi Sekartaji. Nilai-nilai tersebut juga telah dicontohkan oleh perjuangan Kartini melalui emansipasi wanita untuk menuntut keadilan bagi kaum perempuan melalui ranah sektor publik, khususnya di bidang pendidikan. Karya seni “Wening” karya Dyan Anggraini Rais merupakan salah satu bentuk refleksi diri yang dibutuhkan oleh setiap individu di era ini, khususnya perempuan, untuk lebih mengenal dirinya sendiri dan menyadari konstruksi sosial yang telah membentuk dirinya selama ini.